ANALISIS PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN PELANGGAN - Rizky Togelang; Ihwan Susila (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of service quality, product quality, and price on customer satisfaction. This research uses quantitative methods. The population used is all respondents, both men and women who are buyers and customers who have purchased Bluder Bread at Bluder Cokro. The number of samples for this study were 165 respondents. The sampling technique can be classified as non-probability sampling with purposive sampling technique. The data source used in this research is primary data. The data collection technique used is the distribution of questionnaires. The questionnaire was made using a Likert scale format. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The results showed that service quality has a positive effect on customer satisfaction. Product quality has a positive effect on customer satisfaction. Price has a positive effect on customer satisfaction. Keywords: Customer Satisfaction, Price, Product Quality, Service Quality